Mineral Extraction, Human Rights Violations, and the Church’s Social Responsibility in the Democratic Republic of Congo - Emmanuel Ojeifo (African Theological Journal for Church and Society)
The rights and dignity of citizens, especially women and children, in the Democratic Republic of Congo (DRC) are being violated by local and foreign actors, including five United States tech firms, accused of subjecting the people to hazardous and dehumanising working conditions in mining sites, in the quest for the country’s mineral resources, such as cobalt, copper, tin, tungsten, and tantalum. Research has linked the extraction of these minerals to toxic contamination that has resulted in negative health outcomes in women and children and grave violations of human rights such as forced evictions of communities from farmlands and homesteads, sexual assault, arson, and beatings. Locating this mode of violence and exploitation within the neocolonial and neoliberal logic of the sacrifice of African lives, this paper undertakes a critical historical, political, economic, and theological approach to analyse the violence and argues that various stakeholders, especially the church in DRC, have a crucial role to play in standing up against the violence and exploitation going on in DRC and in working for justice, peace, development, and restoration of the dignity and value of human life in the country. At the heart of the paper is the conviction that African lives matter.